Analisa Tingkat Kecemasan pada Tenaga Kesehatan pada Ruang Khusus Isolasi Covid 19 - Veronica Paula; Maria Maxmila Yoche Arkianti; Kinanthi Lebdawicaksaputri (UIMA Press, 2022)
Background: This research is a literature study. PICOT framework is used as strategy to find journals using the keywords “anxiety AND nurses AND COVID-19”. The data sources used are the e-resources database of Indonesian National Library, Pub-med, and Google Scholar in the form of articles or journals. Objectives: This study aims to identify the factors that influence the anxiety of healthcare workers especially nurses during the COVID-19 outbreak. Methods: Inclusion criteria of this study are national and international journals from various databases and related with the research variables namely “Anxiety” and “Nurses for COVID-19 Patients” with article publication time frame in the last 5 years (2016-2021). The exclusion criteria for this study were national and international journals from various databases and not related with research variables; no intervention is given; not about “Anxiety” and “Nurses for COVID-19 Patients”; and the publication time of the article is more than 5 years. Results: Three databases are used: 119 articles found in National Library database; 358 from PubMed; and 836 from Google Scholar. After being disqualified regarding the year of publication for the last 5 years as well as duplication of articles, 327 articles are obtained, and finally, 6 articles that meet the criteria. Conclusion: From the final 6 articles found, most of the healthcare workers experienced anxiety. So, from literature review of 6 research journals, it can be concluded that healthcare workers experienced anxiety when treating patients with COVID-19 which related to additional working hours and workload as well as insufficiency of personal protective equipment.